2022
DOI: 10.1136/bmjopen-2021-055131
|View full text |Cite
|
Sign up to set email alerts
|

Is carotid artery atherosclerosis associated with poor cognitive function assessed using the Mini-Mental State Examination? A systematic review and meta-analysis

Abstract: ObjectivesTo determine associations between carotid atherosclerosis assessed by ultrasound and the Mini-Mental State Examination (MMSE), a measure of global cognitive function.DesignSystematic review and meta-analysis.MethodsMEDLINE and EMBASE databases were searched up to 1 May 2020 to identify studies assessed the associations between asymptomatic carotid atherosclerosis and the MMSE. Studies reporting OR for associations between carotid plaque or intima-media thickness (cIMT) and dichotomised MMSE were meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Two recent systematic reviews have examined the relationship between carotid atherosclerosis and cognition. Baradaran et al [ 3 ] found evidence of an association between carotid artery plaque and poorer cognition based on clinical diagnosis or cognitive testing, while we [ 4 ] found some limited evidence for an adverse association between carotid atherosclerosis and a quantitative measure of cognitive performance, the Mini-Mental State Examination (MMSE). Neither review was able to account fully for confounding due to the disparate nature of the studies included.…”
Section: Introductionmentioning
confidence: 51%
“…Two recent systematic reviews have examined the relationship between carotid atherosclerosis and cognition. Baradaran et al [ 3 ] found evidence of an association between carotid artery plaque and poorer cognition based on clinical diagnosis or cognitive testing, while we [ 4 ] found some limited evidence for an adverse association between carotid atherosclerosis and a quantitative measure of cognitive performance, the Mini-Mental State Examination (MMSE). Neither review was able to account fully for confounding due to the disparate nature of the studies included.…”
Section: Introductionmentioning
confidence: 51%
“…Carotid atherosclerotic plaque progression is associated with an increased risk of stroke and is responsible for 15–20% of ischemic strokes [ 8 10 ]. These plaques are also associated with poor cognitive function [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this difficulty, there are several longitudinal and cross-sectional studies, which have eval-uated this association. The existing studies which have assessed this link between carotid plaque and cognition have demonstrated mixed evidence without a definite consensus, including a recent small meta-analysis finding an association with CIMT, carotid plaque, and minimental status examination [14]. Currently, carotid plaque is primarily considered a major contributor to the development of ischemic stroke rather than a recognized risk factor for cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%